2016
DOI: 10.1158/0008-5472.can-15-2662
|View full text |Cite
|
Sign up to set email alerts
|

In VivoVisualization and Characterization of Epithelial–Mesenchymal Transition in Breast Tumors

Abstract: The activation of the epithelial-to-mesenchymal transition (EMT) program is a critical step in cancer progression and metastasis, but visualization of this process at the single cell level, especially in vivo, remains challenging. We established an in vivo approach to track the fate of tumor cells based on a novel EMT-driven fluorescent color switching breast cancer mouse model and intravital two-photon laser scanning microscopy. Specifically, the MMTV-PyMT, Rosa26-RFP-GFP, and Fsp1-Cre triple transgenic mouse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 35 publications
2
61
0
Order By: Relevance
“…6A). That genes associated with high NF and protrusions have high expression in more aggressive tumors is in line with the idea that aggressive tumors have regions of high cell density driven by high rates of proliferation and have protrusive invasive fronts (Jögi et al 2012;Zhao et al 2016).…”
Section: Derivation Of Morphological Metagenessupporting
confidence: 76%
See 1 more Smart Citation
“…6A). That genes associated with high NF and protrusions have high expression in more aggressive tumors is in line with the idea that aggressive tumors have regions of high cell density driven by high rates of proliferation and have protrusive invasive fronts (Jögi et al 2012;Zhao et al 2016).…”
Section: Derivation Of Morphological Metagenessupporting
confidence: 76%
“…6A). Because high values of cell W/L metagene are indicative of epithelial shape, while lower values are indicative of a more mesenchymal shape (Zhao et al 2016), this suggests that genes associated with epithelial shapes are down-regulated in highly aggressive breast cancers. Moreover, this supports the idea that the activity of the shape-gene network contributes to disease progression.…”
Section: Derivation Of Morphological Metagenesmentioning
confidence: 99%
“…Carcinoma cells undergoing spontaneous EMT have been identified in transgenic mouse mammary tumors and in human breast cancer specimens (4)(5)(6). As EMT may enable carcinoma cells to overcome cell-cell adhesion and to invade neighboring tissue, EMT has been proposed to be a critical event initiating tumor invasion and metastasis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2016) simultaneously observed in vivo EMT alongside changes in cell migration and morphology in the MMTV-PyMT model of invasive and metastatic breast cancer, in which expression of the oncoprotein polyoma middle T antigen (PyMT) under the control of the mouse mammary tumour virus long terminal repeat (MMTV-LTR) drives cancer progression (Lin et al, 2003). Here, IVM can provide insight into single-cell EMT events in their native environment, as well as distinct real-time readouts of drugs targeting the EMT process or cells that have undergone EMT (Zhao et al, 2016). De-regulated expression of the cell-cell junction protein Ecadherin is also often associated with EMT and cell invasiveness (Gregory et al, 2008;Lehmann et al, 2016b).…”
Section: Box 1 Subcellular Imaging Techniquesmentioning
confidence: 99%